Catalytic functionalization of low reactive C(sp3)–H and C(sp2)–H bonds of alkanes and arenes by carbene transfer from diazo compounds. Issue 47 (16th November 2015) - Caballero, Ana; Díaz-Requejo, M. Mar; Fructos, Manuel R.; Olmos, Andrea; Urbano, Juan; Pérez, Pedro J.
Abstract : The direct functionalization of low reactive C(sp 3 )–H and C(sp 2 )–H bonds of alkanes and arenes, respectively, by metal-induced carbene transfer from diazo compounds is reviewed. Abstract : The direct functionalization of low reactive C(sp 3 )–H and C(sp 2 )–H bonds of alkanes and arenes, respectively, by metal-induced carbene transfer from diazo compounds is reviewed. To date, this methodology has enabled the incorporation of CR 1 R 2 moieties from N2 CR 1 R 2 in a chemo, regio, enantio or diastereoselective manner in those substrates with the appropriate selection of metal and ligands.